Innovative Training on HOTS Learning and Digital-Based Literacy and Numeracy Question Development - Tiok Wijanarko; Fitria, Yanti; Ladiva, Hasmai Bungsu; Rifa’i, Muhammad; Melati, Rima; Adrimal, Adrimal; Zuryanty, Zuryanty; Susanto, Nugroho (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Understanding Higher Order Thinking Skills (HOTS) is crucial for elementary school teachers to develop students' critical, creative, and analytical thinking abilities. However, many teachers still face challenges in designing HOTS-based learning and developing science literacy and numeracy questions that are relevant to real-world contexts. This study aimed to provide training for teachers in V Koto Kampung Dalam District, Pariaman, in designing HOTS-based learning and digital-based science literacy and numeracy assessments. The method included pre-test, material presentation, post-test, and guided assignments. The results showed a significant improvement in teachers' understanding and skills, with the average pre-test score for HOTS-based learning increasing from 60.43 to 80, and the average score for developing science literacy and numeracy questions rising from 70 to 90 after the training. These findings highlight the importance of continuous training to enhance teachers' competencies in preparing students to face the challenges of the 21st century